Hsp90 Inhibitor STA9090 induced VPS35 related extracellular vesicle release and metastasis in hepatocellular carcinoma - Wenchong Tan; Jinxin Zhang; Lixia Liu; Manfeng Liang; Jieyou Li; Zihao Deng; Zhenming Zheng; Yaotang Deng; Chenyang Liu; Yan Li; Guantai Xie; Jiajie Zhang; et al. (Translational Oncology, 2022)
Heat shock protein 90 (Hsp90) has been an important therapeutic target for cancer therapy for decades. Unexpectedly, the monotherapy of N-terminal Hsp90 inhibitor STA9090 related clinical trials halted in phase III, and metastases were reported in animal models with the treatment of N-terminal Hsp90 inhibitors. Vacuolar protein sorting-associated protein 35 (VPS35) plays a vital role in endosome-derived EV (extracellular vesicle) traffic in neurodegeneration diseases, but no vps35 related EV were reported in tumors till now. Since tumor derived EVs contributes to metastasis and VPS35 is recently found to be involved in the invasion and metastasis of hepatocellular carcinoma (HCC), whether N-terminal Hsp90 inhibitor STA9090 induced EVs generation and the role of VPS35 in it were explored in this study. We found that N-terminal Hsp90 inhibitor STA9090 upregulated Bclaf1 and VPS35 levels, increased the secretion of EVs, and STA9090-induced-EVs promoted the invasion of HepG2 cells. As the clinical data suggested that the increased Bclaf1 and VPS35 levels correlated with increased metastasis and poorer prognosis in HCC, we focused on the Bclaf1-VPS35-EVs axis to further explore the mechanism of VPS35-related metastasis. The results demonstrated that Bclaf1 facilitated the transcription of VPS35 via bZIP domain, and knockdown of Bclaf1 or VPS35 alleviated pro-metastatic capability of STA9090-induced-EVs. All the results revealed the role of Bclaf1-VPS35-EVs axis on metastasis of HCC, and VPS35 knockdown decreased Hsp90 Inhibitor STA9090 induced extracellular vesicle release and metastasis, which provided a new combination therapeutic strategy to inhibit the metastasis of HCC caused by N-terminal Hsp90 inhibitor induced extracellular vesicles.